The brand loyalty gap between Algerian consumers of local and imported products: An OB-RIF methodological analysis - HERGOUN, Tefaha; LOUNANSA, Ramadan; BOUGROURA, Salah; MOHAMED, Cherif; HOUARIA, Benhalima (International journal of economic perspectives, 2025)
This study aims to analyze the gap in brand loyalty among Algerian consumers toward local and imported products using the Oaxaca–Blinder RIF (Recentered Influence Function) methodology, which allows the decomposition of loyalty differences into explained and unexplained components, The study relied on a sample of 350 Algerian consumers, whose data were collected through a questionnaire covering key variables such as trust, satisfaction, perceived quality, income, education, and age, and Preliminary statistical results using the t-test revealed no significant differences in the average level of loyalty between consumers of local and imported goods, with a gap of only 0.025 that was statistically insignificant. Regression analysis showed that demographic variables such as age, education, and income had weak effects on loyalty, while satisfaction emerged as one of the most influential factors explaining differences between the two groups. demographic characteristics in shaping loyalty. The study concluded that Algerian consumer behavior toward brands is more influenced by mental perceptions and trust gained from experience rather than by direct economic factors, which calls for the development of local marketing strategies focused on strengthening trust and the perceived image quality of national brands.